The Use of Quizizz In Improving Students' Reading Skill - Pradnyadewi, Diah Ayu Manik; Kristiani, Putu Enik (STKIP AGAMA HINDU SINGARAJA, 2021)
Using various learning media in teaching reading are need to avoid the monotonous learning activities which make students easily bored. With increasingly sophisticated technological developments, teachers can apply the Quizizz application as learning media to improve students’ reading skill. The Quizizz application has characteristics such as avatars, themes, memes, and music which are very entertaining in the learning process. At the time they play the game, actually they are reading a lot and learning to understand the meaning of the reading. In addition, the Quizizz Application also has timely feedback, a review section, and repeats tests and follows new quizzes. This literature study reviews some papers in studying the implications of Quizziz and its advantages. The aim of this paper is to share the use of Quizizz Application in improving students reading skill. The findings of this study are expected can be an alternative learning media used by both teacher and students in supporting teaching and learning process in reading.